Treatment for rheumatic polymyalgia - Azamat Makhmudovich Satybaldyev (Современная ревматология)
Glucocorticosteroids (GCs) that provide a good and rapid clinical effect are the drug of choice to treat rheumatic polymyalgia (RP). A review of English language publications on the treatment of RP is given. Thirty (13 randomized and 17 observational) studies of 20 and more patients with RP have been analyzed. Particular emphasis is laid on initial therapy with GCs, evaluation of their different daily doses, schemes for their dosage reduction and treatment termination, and on the frequency of recurrences. Studies dealing with the treatment with prednisone, prednisolone, methylprednisolone, and injectable sustained-release GC formulations are considered. The data of clinical trials of glucocorticoid-sparing agents (methotrexate, azathioprine) during early and maintenance therapy are analyzed. The genetically engineered agents (infliximab, etanercept) investigated in clinical trials are considered to be as alternatives; a case of using rituximab is described. The role of nonsteroidal anti-inflammatory drugs in the treatment of RP is also evaluated. An algorithm is proposed for the management of a patient with RP.